EVALUASI KINERJA DINAS PARIWISATA KEPEMUDAAN DAN OLAH RAGA DALAM RANGKA PENINGKATAN PEMGEMBANGAN WISATA KABUPATEN PACITAN - Meidi Syaflan; Sukanto Sukanto; Mohammad Mahsun (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
In facing competition in the global era, government agencies are required to work more effectively. The increasingly fierce competition causes government agencies to be able to increase competitiveness in order to maintain the viability of government agencies. Government agencies are one of the organizations that bring together people who are commonly referred to as employees to carry out household activities produced by government agencies. Almost all government agencies have the goal of maximizing profits and value for government agencies and also to improve the welfare of owners and employees. Employees are the most important element in determining the progress of a government agency. To achieve the goals of government agencies, employees are needed in accordance with the requirements in government agencies, and must also be able to carry out the tasks that have been determined by government agencies. Every government agency will always try to improve the performance of its employees, with the hope that the goals of government agencies will be achieved. Tourism is one of the service and service industry activities that are the mainstay of Indonesia in order to increase the country foreign exchange in the non-oil and gas sector. The existence of an economic crisis, the tourism sector is expected to be the source of the fastest growth, because tourism infrastructure is not damaged. Number 10 of 2009 concerning Tourism, article 1). Currently, tourism is one of the growing fields in the world.